First record of Chordodes creplin, 1847 (Nematomorpha, Gordioidea) species from a hillstream of Bandarban, Bangladesh - Naser, M Niamul; Hossain, Mostafa Ali Reza; Azadi, M Ali; Khan, M Golam Quader; Alam, M Arshad Ul; Sultana, Selina (Bangladesh Journal of Zoology, 2015)
Abstract not available Bangladesh J. Zool. 42(2): 301-303, 2014